2018
DOI: 10.1001/jamacardio.2018.0398
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sacubitril/Valsartan on Physical and Social Activity Limitations in Patients With Heart Failure

Abstract: clinicaltrials.gov Identifier: NCT01035255.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
75
2
16

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 95 publications
(99 citation statements)
references
References 26 publications
6
75
2
16
Order By: Relevance
“…The implication of different mechanisms of sacubitril–valsartan in the improvement of exercise capacity has been postulated (effect of natriuretic peptides, inhibition of neprilysin, modulation of endorphin–enkephalin system), but the effect of the same remains unclear yet.In recent studies, sacubitril–valsartan improves the functionality of patients through the improvement of domestic activities . Similar studies show an improvement in the distance travelled in the 6MWT .…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…The implication of different mechanisms of sacubitril–valsartan in the improvement of exercise capacity has been postulated (effect of natriuretic peptides, inhibition of neprilysin, modulation of endorphin–enkephalin system), but the effect of the same remains unclear yet.In recent studies, sacubitril–valsartan improves the functionality of patients through the improvement of domestic activities . Similar studies show an improvement in the distance travelled in the 6MWT .…”
Section: Discussionmentioning
confidence: 67%
“…The PARADIGM‐HF (Prospective Comparison of ARNI with an ACE‐Inhibitor to Determine Impact on Global Mortality and Morbidity in Heart Failure) trial showed that sacubitril–valsartan reduced the risk of cardiovascular death or first hospitalization for HF. But there is little evidence regarding the study of the functionality of patients after treatment, and there is little evidence of the drug in elderly patients with multimorbidity …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ACEi or angiotensin receptor blockers (ARB), beta blockers, and mineralocorticoid antagonists (MRA) are the pillars of current management of HFrEF. 42,43 Based on these results, 40,44 sacubitril/valsartan is currently recommended as a replacement for ACEi/ARBs in ambulatory patients with HFrEF who remain symptomatic despite optimal medical treatment. 4 PARADIGM-HF trial showed a reduction in the combined endpoint of CV death or HF hospitalizations, (HR, 0.80; 95% CI, 0.73 to 0.87) as well as all-cause death, CV death and HF hospitalizations alone, and an improvement in symptoms with sacubitril/valsartan vs. enalapril.…”
Section: Neurohormonal Antagonistsmentioning
confidence: 99%
“…41 Quality of life improved and diuretic doses were slightly but significantly reduced in the patients on sacubitril/valsartan, consistent with favourable effects also on symptoms. 42,43 Based on these results, 40,44 sacubitril/valsartan is currently recommended as a replacement for ACEi/ARBs in ambulatory patients with HFrEF who remain symptomatic despite optimal medical treatment. 4, 45 Based on more recent trials, 44,46 it may be considered also in patients hospitalized for acute HF, including also those with new onset HF.…”
Section: Neurohormonal Antagonistsmentioning
confidence: 99%